Continuous Finite Element Methods of Molecular Dynamics Simulations. (29th July 2015) - Tang, Qiong; Liu, Luohua; Zheng, Yujun
Abstract : Molecular dynamics simulations are necessary to perform very long integration times. In this paper, we discuss continuous finite element methods for molecular dynamics simulation problems. Our numerical results aboutA B diatomic molecular system andA 2 B triatomic molecules show that linear finite element and quadratic finite element methods can better preserve the motion characteristics of molecular dynamics, that is, properties of energy conservation and long-term stability. So finite element method is also a reliable method to simulate long-time classical trajectory of molecular systems.